Die operative Dekompression des Ramus superficialis des Nervus radialis: das Wartenberg-Syndrom = Surgical decompression of the superficial radial nerve : Wartenberg syndrome - Spies, Christian; Unglaub, Frank (Operative Orthopädie und Traumatologie, 2016)
Objective: Open decompression of the superficial radial nerve is performed at the distal forearm in cases of circumscript entrapment. Broad-based entrapments can be treated by endoscopically assisted decompression. Indications: Entrapment of the nerve along its course between the brachioradialis and extensor carpi radialis longus muscles or tendons. Persistent neuropathic pain with Tinel’s sign. Numbness distal to the entrapment in accordance to nerval innervation. Futile conservative treatment. Pathological electrophysiological findings. Contraindications: Endogeneous neuropathy, bleeding disorders, anticoagulation medication. Surgical technique: Longitudinal skin incision at the Tinel’s sign at the forearm. The subcutaneous tissue is dissected until forearm fascia is detected. The fascia is opened cautiously under direct visualization and the superficial radial nerve is identified. In cases of broad-based entrapments, endoscopically assisted decompression can be performed. The dissector with attached optical device is introduced proximally and distally. Blunt mobilization using the dissector and preparation with the Metzenbaum scissors release the superficial radial nerve sufficiently. Postoperative management: Bandaging allowing immediate motion, removal of sutures after 14 days, avoidance of excessive use for 2 weeks. Results: Surgical decompression of the superficial radial nerve yields good to excellent results regarding pain reduction and sensory function.
Gesehen am 23.04.2019
Online publiziert: 26. Oktober 2015